[18F]-Group 13 fluoride derivatives as radiotracers for positron emission tomography. (9th November 2015) - Chansaenpak, Kantapat; Vabre, Boris; Gabbaï, François. P.
Abstract : This article reviews the radiofluorination chemistry of group 13 derivative as well as their use for 18F-PET Imaging. Abstract : The field of 18 F chemistry is rapidly expanding because of the use of this radionuclide in radiotracers for positron emission tomography (PET). Until recently, most [ 18 F]-radiotracers were generated by the direct attachment of 18 F to a carbon in the organic backbone of the radiotracer. The past decade has witnessed the emergence of a new strategy based on the formation of an 18 F-group 13 element bond. This approach, which is rooted in the field of fluoride anion complexation/coordination chemistry, has led to the development of a remarkable family of boron, aluminium and gallium [ 18 F]-fluoride anion complexing agents which can be conjugated with peptides and small molecules to generate disease specific PET radiotracers. This review is dedicated to the chemistry of these group 13 [ 18 F]-fluorides anion complexing agents and their use in PET. Some of the key fluoride-binding motifs covered in this review include the trifluoroborate unit bound to neutral or cationic electron deficient backbones, the BF2 unit of BODIPY dyes, and AlF or GaF3 units coordinated to multidentate Lewis basic ligands. In addition to describing how these moieties can be converted into their [ 18 F]-analogs, this review also dicusses their incorporation into bioconjugates for application in PET.